Preparation of financial policy to increase timing of inpatient billing information of hospital “X” - Abdi Agus Youandi; Kurnia Widyaningrum; Navis Yuliansyah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Background: One of the main problems encountered in RS X is the timing of inpatient billing information that has not been ≤ 2 hours. The focus of the study was to begin when the DPJP said the patient was allowed to go home until the patient received inpatient billing information. This study aims to explore the root of the problem has not reached the standard speed of inpatient billing information. Method: This research method is qualitative research. The study was conducted at hospital X from September to October 2017. Data were collected using literature study method, document review, unit observation, in-depth interview, focus group discussion (FGD). Result: Delay of billing information due to slow recording and recording differences. Differences in recording arise due to duplicate work of nurses who have other activities. Duties nurses not only provide patient care but have the administrative task. Conclusion: The speed of inpatient billing information information has not been standardized ≤ 2 hours due to duplicate of work of nurse having other activity. The solution to the problem is the need for revised policies and SOPs that regulate the duties, authority and responsibilities of each staff in more detail.